IMPLEMENTASI PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN KOGNITIF SAINS ANAK USIA 5-6 TAHUN DI RA ANNUR ASSALAFY TUMPANG PACARKELING KEJAYAN PASURUAN: IMPLEMENTATION OF A SCIENTIFIC APPROACH TOWARDS THE COGNITIVE SCIENCE ABILITIES OF 5-6 YEAR-OLD CHILDREN AT RA ANNUR ASSALAFY TUMPANG PACARKELING KEJAYAN PASURUAN - Ismawati, Putri; Hanifah, Hanifah (Universitas Islam Malang, 2020)
This study aims to determine the effectiveness of the implementation of a scientific approach to the cognitive abilities of children aged 5-6 years at RA Annur Assalafy Tumpang Pacarkeling Kejayan Pasuruan. By using a scientific approach with an understanding of 5M (observing, asking, collecting information, reasoning/associating, making conclusions and communicating) it is hoped that the learning process at RA, especially in the development of cognitive science, can attract children's attention so that children's interest in learning is very good so that aspects of child development can be achieved as expected. This study uses qualitative research that describes the researcher's understanding in implementing a scientific approach to the learning process, especially cognitive science. The data were obtained through interviews, observations, and documentation. The results of the study are (1) The researcher's initial understanding of the cognitive science approach is quite good. (2) learning planning in a scientific approach in compiling daily learning implementation plans (RPPH) and media has referred to the appropriate steps because the researcher has received training on campus so that in compiling daily learning implementation plans (RPPH) the researcher is quite good. (3) The implementation of cognitive science learning using a synthetic approach in preliminary activities, core activities, and closing activities is quite good with an understanding of the 5 M (observing, asking, gathering information, reasoning/associating, drawing conclusions and communicating). Learning is child-centered. Children are more active in learning than teachers, which results in children's thinking skills being higher.